-3(4T-1)=-(t-14)

Simple and best practice solution for -3(4T-1)=-(t-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4T-1)=-(t-14) equation:


Simplifying
-3(4T + -1) = -1(t + -14)

Reorder the terms:
-3(-1 + 4T) = -1(t + -14)
(-1 * -3 + 4T * -3) = -1(t + -14)
(3 + -12T) = -1(t + -14)

Reorder the terms:
3 + -12T = -1(-14 + t)
3 + -12T = (-14 * -1 + t * -1)
3 + -12T = (14 + -1t)

Solving
3 + -12T = 14 + -1t

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -12T = 14 + -3 + -1t

Combine like terms: 3 + -3 = 0
0 + -12T = 14 + -3 + -1t
-12T = 14 + -3 + -1t

Combine like terms: 14 + -3 = 11
-12T = 11 + -1t

Divide each side by '-12'.
T = -0.9166666667 + 0.08333333333t

Simplifying
T = -0.9166666667 + 0.08333333333t

See similar equations:

| 9h-27=36 | | 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x | | 32-66= | | x-34=5x+2 | | (2x+6)+(5x+6)= |

Equations solver categories